STRATEGI PERHUBUNGAN AWAM ISLAM DAN PERANANNYA DALAM MEMBANGUNKAN MASYARAKAT MADANI: Islamic Public Relations Strategy and its Role in Developing Civil Society - Ridzuan, Ahmad Al-Munzir; Kamri, Nor 'Azzah; Mohd Yusoff, Mohd Yakub@Zulkifli (Jurnal Syariah, 2024)
This study examined the Islamic public relations strategy and its role in developing civil society. Civil society, as envisioned by the Government’s Malaysia Madani, aims to create an inclusive and harmonious society in diverse demographic in Malaysia where there are differences in culture, religion and belief. In this context, the practice of Islamic public relations is a key player in this development. To explore this a qualitative approach through library research was chosen, involving an in-depth study of the Qur’an and previous studies related to this topic. This study identified five strategies that can be applied in public relations practice, each of which is fundamental realiinge the Government’s vision of a developed civil society.